1975
DOI: 10.1111/j.1432-1033.1975.tb04149.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Heteroaromatic Compounds with Nucleic Acids

Abstract: In the present paper we report the results of a study on the base specificity and affinity of eight dyes potentially able to interact with DNA. These compounds include four triphenylmethane dyes used in histochemistry, auramine, "Hoechst 33258" and two acridines substituted with t-butyl groups. They were selected with regard to their inability to intercalate between the base pairs of helical polynucleotides due to structural limitations.Hydrodynamic studies performed with the DNA complexes of crystal violet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(126 citation statements)
references
References 19 publications
9
116
1
Order By: Relevance
“…As previously reported (22, 36, 37), a reverse (R-band) staining pattern is produced if a G-C specific energy donor (chromomycin A3) (3) is used together with an A-T specific M 33258 Hoechst ( A ), 33258 Hoechst followed by energy acceptor (methyl green) (33). Chromosomal regions exhibiting dull quinacrine fluorescence (e.g., most of human chromosome 22) fluoresce brightly with this latter combination.…”
Section: Resultssupporting
confidence: 54%
“…As previously reported (22, 36, 37), a reverse (R-band) staining pattern is produced if a G-C specific energy donor (chromomycin A3) (3) is used together with an A-T specific M 33258 Hoechst ( A ), 33258 Hoechst followed by energy acceptor (methyl green) (33). Chromosomal regions exhibiting dull quinacrine fluorescence (e.g., most of human chromosome 22) fluoresce brightly with this latter combination.…”
Section: Resultssupporting
confidence: 54%
“…H33258 did not compete for 7-AMD binding sites, since similar results (546-nm excitation) were obtained when H33258 was omitted from the staining buffer. This was to be expected, since 7-AMD shows G-C specificity (16,19,25), while H33258 preferentially binds to A-T stretches (16,20,25). It has been shown that H33258 and 7-AMD do not compete for binding sites when bound to DNA (16,25,. Seventy percent ethanol-fixed cells were stained with acridine orange (Fluka) in 0.15 M NaC1, 5 mM EDTA, 10 mM Tris-HCl (pH = 7.4) at < 0.6 -lo6 cells/ml after one wash in the same buffer.…”
Section: Stainingmentioning
confidence: 84%
“…1 The results of the DNasel experiments are also intriguing and indicate that 7-AMD binding in formaldehydefixed chromatin of leucocytes is restricted by the topological state of DNA (i.e., that the double-stranded DNA is quasicircular). Binding of 7-AMD, a n intercalator, increased after mild DNasel digestion, while the binding of H33258, a probe which binds externally along three A-T basepairs (20), decreased monotonically. Binding of intercalators at high concentrations is assumed to increase after nicking of DNA (3,24), which may explain the enhanced levels of bound 7-AMD in DNasel-digested chromatin.…”
Section: 6)mentioning
confidence: 99%
“…However, in view of the Miiller and Crothers' study (21) indicating G.C specificity, the most likely explanation for low $JR of natural DNA is preferential intercalation of PY between the base pairs containing guanine at this low binding density, rather than the long-distance effects of this base.…”
Section: Pm)mentioning
confidence: 94%